Iron deficiency in a male with multiple myeloma. (16th December 2010) - Singh, V; Bhattarai, N; Panda, M
Abstract : A 58-year-old man with long standing unexplained iron deficiency anaemia presented with severe hypercalcaemia and was subsequently diagnosed with multiple myeloma. Anaemia in multiple myeloma is usually normochromic and normocytic.1 To our knowledge, there are no reported cases in the English literature of true iron deficiency associated with multiple myeloma. Our case highlights the importance of pursuing the aetiology of iron deficiency, especially in a middle aged male. It also reinforces the fact that severe hypercalcaemia usually has a malignant aetiology.